2005
DOI: 10.1159/000085623
|View full text |Cite
|
Sign up to set email alerts
|

Bacteremia in Patients with Hematological Malignancies

Abstract: Background: An appropriate regimen in the empirical therapy of neutropenic fever episodes must be individualized at each institution. Hospitals have different patterns of microbial isolates and antibiotic resistance that must be taken into account. The aim of this study was to investigate isolates of bacteremia and their antibiotic susceptibility in patients with hematological malignancies. Methods: All positive blood cultures at a medical center in Taiwan between 1999 and 2002 from patients with hematological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 47 publications
5
28
2
Order By: Relevance
“…Infection mortality was higher in the group with inadequate empirical therapy group than in the adequate therapy group. These findings were in accord with some studies [11,17,18]. The statistical difference between the crude mortality and infection mortality was probably due to the condition of patients at onset of symptoms and clinical features.…”
Section: Discussionsupporting
confidence: 92%
“…Infection mortality was higher in the group with inadequate empirical therapy group than in the adequate therapy group. These findings were in accord with some studies [11,17,18]. The statistical difference between the crude mortality and infection mortality was probably due to the condition of patients at onset of symptoms and clinical features.…”
Section: Discussionsupporting
confidence: 92%
“…The predominant etiology of BSIs in cancer patients with neutropenia has been reported to be gram-positive organisms in recent studies. 16e18 However, previous studies in Taiwan 6,19 and our data showed that GNB remain being responsible for most causative microorganisms of BSIs in cancer patients who were neutropenic or not. A high prevalence of Enterobacteriaceae bacteremia in neutropenic cancer patients with BSIs, at least 51.4%, may be explained by breaking down of gastrointestinal mucosal barrier.…”
Section: Discussionmentioning
confidence: 64%
“…21 Whether underlying malignancy adversely affects the clinical outcome of patients with bacteremia is controversial. In a study of K pneumoniae bacteremia, malignancy served as an independent variable for mortality.…”
Section: Discussionmentioning
confidence: 99%